Hearing impairment among Korean farmers, based on a 3-year audiometry examination - Sujin Lee; Kyungsuk Lee; Soo-Jin Lee (Annals of Agricultural and Environmental Medicine, 2019)
Introduction and objective Work noise exposure among farmers can cause hearing loss. Farmers are exposed to hazardous noise from equipment and domestic animals, and experience high rates of noise-induced hearing loss. The aim of our study was to evaluate the hearing thresholds of farmers in Korea. This study is the first to evaluate hearing impairment in Korean farmers nationwide. There have been few studies that have performed audiometric testing to measure hearing impairment at the national level in Korea.